Tuberculosis prevention and care in Korea: Evolution of policy and practice - Unyeong Go (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2018)
Tuberculosis (TB) in Korea remains a serious health problem with an estimated 77 per 100,000 incidence rate for 2016. This makes Korea as the only OECD country with high incidence of TB. The government has increased budgets and strengthened patient management policies since 2011. The management of latent tuberculosis was added to the response with strengthened and extensive contact investigations in the five-year tuberculosis control plan (2013–2017) and implementation was established in 2013. Due to these efforts Korea has achieved an average 5.2% reduction annually in tuberculosis incidence rate between 2011 and 2016. To further expedite the reduction of the TB burden the government has introduced additional measures including mandatory screening of latent tuberculosis infection for community workers in congregate settings including daycare centers for children, kindergarten, and teachers in schools and health care workers in clinics and hospitals to solve the problems identified through contact investigations in 2017.Providing high quality free diagnosis and treatment of active TB including for multidrug resistant TB combined with active contact investigations is the mainstay of the current programmatic response in Korea. However, the limitation of existing tools for LTBI pose challenge including absence of best mechanism for effective communication with professionals and the public, the need for at least 3 months of treatment and the risk of side effects. Developing effective tools will help to overcome these challenges. Keywords: Tuberculosis, Latent tuberculosis infection, End TB, Contact investigations, Epidemiology